Dual-earner migration in Britain: earnings gains, employment, and self-selection - Birgitta Rabe (University of Essex, Institute for Social and Economic Research (ISER), 2006)
This paper examines how spouses in dual-earner couples in Britain weigh each partners expected wage growth in the decision to migrate. Previous research suggests that husbands job prospects dominate the migration choice irrespective of their relative earnings potential. Based on British panel data this paper employs an endogenous switching model and estimates wage change differentials of migrating vs. staying for husbands and wives corrected for double selectivity of migration and employment. The analysis shows that dual-earner couples put roughly equal weights on each partners expected wage gains when deciding to migrate. Moreover, migrant wives employment declines temporarily and there are significant selection effects in migration and employment among non-migrants.
Keywords: 330